Effective Thinking: Representation Implementation Word Square Learning Model on Islamic Religious Education - Bahar Agus Setiawan; Sofyan Rofi; Tri Endang Jatmikowati; Dahani Kusumawati; Finta Meifah Nada (Jurnal Pendidikan Islam Indonesia, 2023)
The philosophy of the learning process carries out at least five main dimensions, namely active, innovative, creative, effective and fun. The content of Islamic religious education learning materials such as the Koran, hadith, morality and others, requires a plurality of learning models. Harmony between the content of learning materials and the models used was a necessity that cannot be ruled out. One of the learning models that can be used in learning Islamic religious education is the word square. This study aims to examine more deeply the benefits of word squares in improving and developing the ability to think effectively as an indicator of the learning model. The research instrument used written interviews, with a questionnaire model with five component indicators of the ability to think effectively. The number of respondents was 35 students of class X at SMAN Darussholah Singojuruh Banyuwangi. The average research results for measuring the five component indicators of the ability to think effectively reach 93.7 per cent which confirms that the word square learning model played a role in improving and developing students' effective thinking.